THE RELATIONSHIP BETWEEN THE LEVEL OF INTERLEUKIN-6 AND PROCALCITONIN IN SEVERE SEPSIS PATIENTS AT THE ADAM MALIK HOSPITAL - Sesily C Nainggolan; Adi Koesoema Aman; Achsanudin Hanafie (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Severe sepsis is defined as sepsis that is accompanied by one or more organ dysfunctions, hypotension or hypoperfusion (decreased renal function, hypoxemia, lactic acidosis, oliguria, mental status changes). Macrophages and monocytes produced Procalcitonin (PCT) in serious bacterial infections and sepsis. Interleukin-6 (IL-6) is an interleukin that acts as proinflammatory cytokines. The high IL-6 level is due to chronic inflammation and sepsis. IL-6 is found increased more rapidly in the acute phase, so it can be used to evaluate early phase infection and sepsis. The purpose of this study was to find out IL-6 and PCT levels in severe sepsis patients. This study was a cross-sectional observational study. The subjects were sepsis patients treated in Adam Malik Hospital on Jan-Mar 2016. Statistical data was analyzed using SPSS and the Spearman rank correlation, with significant p-value < 0.05. IL-6 was tested using Chem Well 9210 series. Procalcitonin examination was done by mini VIDAS BRAHMS PCT. There were 40 people observed as subjects in this study, 26 males (65%) and 14 females (35%). The average age of male was 49.42 ± 18.19 years old, the youngest 18 years old, and the oldest 79 years old. The average age of females 57.35 ± 20.73, the youngest 18 years old, and the oldest 87 years old. The average of IL-6 was 10862.12 ± 25489.16 and PCT was 9666.73 ± 10540.13. Spearman rank test was also used, the value of r = 0.176 and p = 0.277. The conclusion is there is no significant correlation between IL-6 and PCT. There is no significant correlation between IL-6 and PCT levels in severe sepsis patients.